Six new species of Aculus Keifer from Tibet Autonomous Region, China (Acari: Eriophyoidea: Eriophyidae: Phyllocoptinae) - Song, Zi-Wei; Xue, Xiao-Feng; Hong, Xiao-Yue (Zootaxa, 2009)
Six new species of Aculus Keifer from China are described and illustrated. They are Aculus vignaus sp. nov. on Vigna vexillata (L.) Rich. (Fabaceae); Aculus jasmini sp. nov. on Jasminum humile L. (Oleaceae); Aculus sorbariae sp. nov. on Sorbaria sorbifolia (L.) A. Br. (Rosaceae); Aculus tibetsalicinus sp. nov. on Salix sp. (Salicaceae); Aculus lhasasorbariae sp. nov. on Sorbaria sp. (Rosaceae) and Aculus cheilophilanus sp. nov. on Salix cheilophila Schneid (Salicaceae). All the eriophyoid mite species described here are vagrants on the undersurface of host leaves. A key to the Chinese Aculus species is also provided.